Patterns of physical activity among government and private school children in coastal Karnataka - Mahaur, Gunjan; Badiger, Sanjeev (International Journal Of Community Medicine And Public Health, 2018)
Background: Higher level of physical activity is associated with low mortality rates for both adults and children. Those who are moderately active on a regular basis have lower mortality rates than those who are least active. Methods: A cross sectional study was conducted in private and government schools of Mangalore city from October 2015 to July 2017, study population was between 13 and 15 years adolescents. Sample size of 1000 was been obtained by using Proportional probability sampling. A pretested validated questionnaire was used for data collection. Data entry was done in Microsoft Excel and data analysis was done in SPSS version 22. Results: Out of 1000 students, 130 was from government school and 870 from private schools. Physical activity level among government school children was found to be more than private school children (p<0.005). Government school children had more number of underweight students (70%) compared to private school children (37.5%). Conclusions: This study showed that more research is necessary to evaluate intermediate factors and to determine which interventions are likely to be most effective to prevent childhood and adolescent obesity.